Complete Chloroplast Genome Sequences and Comparative Analysis of Chenopodium quinoa and C. album - Hong, Su-Young; Cheon, Kyeong-Sik; Yoo, Ki-Oug; Lee, Hyun-Oh; Cho, Kwang-Soo; Suh, Jong-Taek; Kim, Su-Jeong; Nam, Jeong-Hwan; Sohn, Hwang-Bae; Kim, Yul-Ho (Frontiers in Plant Science, 2017)
The Chenopodium genus comprises approximately 150 species, including C. quinoa and C. album, two important crops with high nutritional value. To elucidate the phylogenetic relationship between the two species, the complete chloroplast (cp) genomes of these species were obtained by next generation sequencing. We performed comparative analysis of the sequences and, using InDel markers, inferred phylogeny and genetic diversity of the Chenopodium genus. The cp genome is 152,167 bp (C. quinoa) and 152,099 bp (C. album) long. In total, 119 genes (78 protein-coding, 37 tRNA, and 4 rRNA) were identified. We found 14 (C. quinoa) and 15 (C. album) tandem repeats (TRs); 14 TRs were present in both species and C. album and C. quinoa each had one species-specific TR. The trnI-GAU intron sequences contained one (C. quinoa) or two (C. album) copies of TRs (66 bp); the InDel marker was designed based on the copy number variation in TRs. Using the InDel markers, we detected this variation in the TR copy number in four species, C. hybridum, C. pumilio, C. ficifolium, and C. koraiense, but not in C. glaucum. A comparison of coding and non-coding regions between C. quinoa and C. album revealed divergent sites. Nucleotide diversity greater than 0.025 was found in 17 regions—14 were located in the large single copy region, one in the inverted repeats, and two in the small single copy region. A phylogenetic analysis based on 59 protein-coding genes from 25 taxa resolved Chenopodioideae monophyletic and sister to Betoideae. The complete plastid genome sequences and molecular markers based on divergence hotspot regions in the two Chenopodium taxa will help to resolve the phylogenetic relationships of Chenopodium.